Misinterpretation of Arabic Music as Salawat: A Study of Cultural Representation in Indonesian Music - Sa’diyah, Nikmatus (Fast in Humanities, 2026)
This study aims to examine how cultural representation and digital media practices shape the reinterpretation of non-religious Arabic music as salawat in Indonesian society. In this context, Arabic cultural elements are often strongly associated with Islamic identity, leading to the perception that Arabic-language music is inherently religious. This phenomenon reflects the dynamic nature of meaning construction within cultural and media environments. This study employs a qualitative approach within cultural and media studies, using a case study design. Data consist of six non-religious Arabic songs and 60–90 related digital media contents from TikTok and YouTube collected between 2023 and 2025. Data are gathered through ethnographic observation and analyzed using qualitative content analysis and semiotic analysis, guided by representation theory and the encoding/decoding model. The findings show that reinterpretation is a structured process. Cultural representation establishes a dominant code linking Arabic culture with Islam. Musical elements and visual imagery reinforce religious associations, while digital media practices frame and amplify these meanings. Audience interpretation further consolidates the reinterpretation. The study concludes that musical meaning is socially constructed through cultural symbols, media practices, and audience interpretation, highlighting the role of digital media in shaping contemporary religiosity